Complementary and Synergistic Therapeutic Effects of Compounds found in Kampo Medicine: Analysis of daikenchuto - Kono, Toru; Shimada, Mitsuo; Yamamoto, Masahiro; Kaneko, Atushi; Oomiya, Yuji; Kubota, Kunitsugu; Kase, Yoshio; Lee, Keiko; Uezono, Yasuhito (Frontiers in Pharmacology, 2015)
Herbal medicines have been used in Japan for more than 1500 years and traditional Japanese medicines (Kampo medicines) are now fully integrated into the modern healthcare system. In total, 148 Kampo formulae are officially approved as prescription drugs and covered by the national health insurance system in Japan. However, despite their long track record of clinical use, the multi-targeted, multi-component properties of Kampo medicines, which are fundamentally different from Western medicines, have made it difficult to create a suitable framework for conducting well designed, large-scale clinical trials. In turn, this has led to misconceptions among western trained physicians concerning the paucity of scientific evidence for the beneficial effects of Kampo medicines. Fortunately, there has been a recent surge in scientifically robust data from basic and clinical studies for some of the Kampo medicines, e.g., daikenchuto (TU-100). Numerous basic and clinical studies on TU-100, including placebo-controlled double-blind studies for various gastrointestinal disorders, and absorption, distribution, metabolism and excretion (ADME) studies, have been conducted or are in the process of being conducted in both Japan and the USA. Clinical studies suggest that TU-100 is beneficial for postoperative complications, especially ileus and abdominal bloating. ADME and basic studies indicate that the effect of TU-100 is a composite of numerous actions mediated by multiple compounds supplied via multiple routes. In addition to known mechanisms of action via enteric/sensory nerve stimulation, novel mechanisms via the TRPA1 channel and two pore domain potassium channels have recently been elucidated. TU-100 compounds target these channels with and without absorption, both before and after metabolic activation by enteric flora, with different timings and possibly with synergism.